In Vitro Model of Vascular Remodeling Under Microfluidic Perfusion - Kotaro Nishikata; Kimisato Doi; Nobuyoshi Kaneoya; Masataka Nakamura; Nobuyuki Futai (Micromachines)
We developed a portable microfluidic system that combines spontaneous lumen formation from human umbilical endothelial cells (HUVECs) in fibrin–collagen hydrogels with active perfusion controlled by a braille actuator. Adaptive interstitial flow and feedthrough perfusion switching enabled the successful culture of spontaneously formed naturally branched lumens for more than one month. We obtained many large-area (2 mm × 3 mm) long-term (more than 30 days per run) time-lapse image datasets of the in vitro luminal network using this microfluidic system. We also developed an automatic image analysis pipeline to extract the morphology of the lumen network and node–edge network structure weighted with segmentwise flow parameters. The automatic lumen area measurements revealed that almost all lumens were successfully cultured in this system for approximately 50 days, following the meshwork, sprouting, remodeling, stability, and erosion stages. We found that the optimization of the lumen network during the remodeling stage can be explained by the decrease in the betweenness centrality of the WSS-weighted network and the increase in the strength centrality of the flow-rate-weighted network.